Evaluation of types and concentration of bile salts impact on physical properties of nisoldipine-loaded bilosomes - Ghada Hamid Naji; Fatima J. Al Gawhari (Pensoft Publishers, 2024)
Background: Bilosomes are lipid vesicles that exhibit flexibility and deformability. They consist of phospholipids and amphiphilic bile salts. Compared to the normal vesicular systems such as liposomes and niosomes, bilosomes provide several notable advantages, including simplified manufacturing, cost-effectiveness, and enhanced stability. Aim: The main objective of the present work was to evaluate the effect of different bile salts on the physical properties that include entrapment efficiency, vesicle size, and polydispersity index(PDI). In addition, in vitro drug release for nisoldipine (NSD) loaded bilosomes was evaluated. Methods: Nisoldipine-loaded bilosomes were made using a thin film hydration technique. Cholesterol along with surfactant (span 60) was employed, and the formulation also contained several different bile salts, including sodium deoxycholate (SDC), sodium glycocholate (SGC), and sodium taurocholate (STC). Results: The developed NSD bilosomes exhibited an entrapment efficiency ranging from 44.2 ± 0.3 to 82.36 ± 0.80% and a vesicle size diameter in the nanometric dimensions (166 ± 1.83 to 237.8 ± 3.3 nm). An in-vitro release study revealed that formulas prepared with SDC bile salts showed higher drug release than SGC and STC formulas. Increasing the bile salt amount from 5 mg to 10 mg increases entrapment efficiency with increasing vesicle size. Further increase in bile salt led to decreased entrapment efficiency with increased vesicle size. SDC gives the best result in terms of entrapment efficiency and acceptable size. STC provides the largest particle size due to its high molecular weight compared to SGC and SDC. Conclusion: The SDC bile salt component is better suited for manufacturing NSD bilosomes. This is because this component yields the best results regarding high entrapment efficiency, nano size, and prolonged drug release.